A new rapid synthesis of thermoelectric Sb2Te3 ingots using selective laser melting 3D printing. (1st March 2021) - Shi, Jianxu; Chen, Xiaoming; Wang, Wanjun; Chen, Hualing
Abstract: The conventional synthesis and forming process methods of commercialized thermoelectric materials and thermoelectric devices are energy and time consuming. Fortunately, advanced 3D printing techniques enable simplification for the rapid fabrication of thermoelectric materials. Herein, we report a new synthesis method of Sb2 Te3 by selective laser melting (SLM) printing technique. A mixture of individual elemental powder of Sb and Te serves as starting materials for the SLM process. The effect of the high laser energy density on the synthesized Sb2 Te3 structure and thermoelectric performance is also investigated, and the optimal process parameters are determined. The phase transition process for the Sb/Te powder during SLM is imitated by performing a thermogravimetric analysis (TGA) simultaneously. The power factor of the ingot prepared by SLM increases up to 19 μW/(cm K 2 ) at 50 °C. These results indicate that SLM can effectively produce Sb2 Te3 -based materials. This work opens a new route for the design and synthesis of thermoelectric materials and corresponding devices.